Laminins and cancer stem cells: Partners in crime?. (August 2017) - Qin, Yan; Rodin, Sergey; Simonson, Oscar E.; Hollande, Frédéric
Abstract: As one of the predominant protein families within the extracellular matrix both structurally and functionally, laminins have been shown to be heavily involved in tumor progression and drug resistance. Laminins participate in key cellular events for tumor angiogenesis, cell invasion and metastasis development, including the regulation of epithelial-mesenchymal transition and basement membrane remodeling, which are tightly associated with the phenotypic characteristics of stem-like cells, particularly in the context of cancer. In addition, a great deal of studies and reports has highlighted the critical roles of laminins in modulating stem cell phenotype and differentiation, as part of the stem cell niche. Stemming from these discoveries a growing body of literature suggests that laminins may act as regulators of cancer stem cells, a tumor cell subpopulation that plays an instrumental role in long-term cancer maintenance, metastasis development and therapeutic resistance. The accumulating evidence in this emerging research area suggests that laminins represent potential therapeutic targets for anti-cancer treatments against cancer stem cells, and that they may be used as predictive and prognostic markers to inform clinical management and improve patient survival.